Evaluation of Tpeak-Tend interval and Tpeak-end/QT ratio in patients with Sarcoidosis - Ucsular, Fatma; Karadeniz, Gülistan; Karadeniz, Cem; Yalnız, Enver; Demir, Melike (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Tp-e interval which represents the interval between the peak and the end of the T-wave on electrocardiogram (ECG), can be used as a marker of transmural dispersion of repolarization. Also, Tp-e/ QT and Tp-e/QTc ratios are used as an index of arrhythmogenesis. Prolonged Tp-e interval and Tp-e/QT ratio was found associated with sudden cardiac death in different clinical conditions. Novel ventricular repolarization parameters, Tp-e interval, Tp-e/QT and Tp-e/QTc ratios have not been evaluated in patients with sarcoidosis without cardiac symptoms previously. Therefore, we investigated Tp-e interval in patients with pulmonary sarcoidosis. Methods: Sixty-one consecutive patients diagnosed with biopsy-proven pulmonary sarcoidosis were retrospectively reviewed. The 12-lead ECG examinations were performed at speed of 25 mm/s while the patients were in supine position. QT dispersion, Tp-e intervals and Tp-e/QT ratio were measured. Results: Comparison of ECG parameters between two groups showed a significantly higher average heart rate (p< 0.05) in the patients with sarcoidosis than controls. QT dispersion was higher in patients group. Tp-e interval was significantly prolonged in the study group compared to the control group (92±21 ms and 85±14 ms, respectively; p< 0.05). Tp-e/QT and Tp-e/QTc ratios were significantly higher in patients with sarcoidosis compared to control subjects (all p values < 0.05). Conclusions: The novel repolarization parameters Tp-e interval, Tp-e/QT and Tp-e/ QTc ratios are increased in patients with sarcoidosis without any cardiac symptoms. These parameters might be used as a marker for predicting the ventricular arrhythmias and sudden cardiac death in patients with sarcoidosis.